1988
DOI: 10.1007/bf00315839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the notochord on the differentiation of a floor plate area in the neural tube of the chick embryo

Abstract: The role of a notochord fragment on the origin of an additional floor plate area in the neural tube is investigated by quantitative morphological methods. In 1.5 to 2 day chick embryos a notochordal fragment was implanted in close apposition to the lateral wall of the neural groove in the region between prospective wing and leg bud. At 4 days, adjacent to the implant a distinct area of the neural wall was present, which resembled the natural floor plate with respect to its thickness, the abluminal location of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(81 citation statements)
references
References 21 publications
4
77
0
Order By: Relevance
“…It induces the differentiation of the floor plate by contact dependent signal(s) and of motor neurons by diffusion signal(s) (28)(29)(30). Removal of the notochord leads to the formation of spinal chord that is devoid of floor plate, motor-neurons, and ventral neurons (31), whereas grafted notochord gives rise to additional ectopic floor plate and motor neurons (31,32). In addition, the notochord has also been implicated in other developmental processes such as the formation of the vertebrate cartilage (33,34) and the modulation of neural crest cell migration and differentiation (35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It induces the differentiation of the floor plate by contact dependent signal(s) and of motor neurons by diffusion signal(s) (28)(29)(30). Removal of the notochord leads to the formation of spinal chord that is devoid of floor plate, motor-neurons, and ventral neurons (31), whereas grafted notochord gives rise to additional ectopic floor plate and motor neurons (31,32). In addition, the notochord has also been implicated in other developmental processes such as the formation of the vertebrate cartilage (33,34) and the modulation of neural crest cell migration and differentiation (35).…”
Section: Resultsmentioning
confidence: 99%
“…The differentiation of floor plate cells and motor neurons is dependent on inductive signals emanating from the notochord (31,40,41). Removal of the notochord at stage 10 prevents later floor plate and ventral neuronal differentiation (31), while conversely, notochord grafts (stages 10-12) placed adjacent to the neural tube induce ectopic floor plate and ventral neuron differentiation 2 days later (32). In addition, it has been shown that, in vivo, the notochord and the floor plate possess also a dorsoventral polarizing activity on the paraxial mesoderm (somites) (42).…”
Section: Discussionmentioning
confidence: 99%
“…Floor plate cells are derived from the organiser, as is the notochord, which is a rod-like embryonic structure underlying the floor plate (Jessell et al, 1989;Woo and Fraser, 1995;Catala et al, 1996). Notochord induces floor plate in amniote embryos when combined with neural tissue (van Straaten et al, 1988;Placzek et al, 1990), suggesting an instructive role of notochord in floor plate development. The secreted signalling molecule Sonic hedgehog (Shh), which is expressed in the notochord and the floor plate (Echelard et al, 1993;Krauss et al, 1993;Riddle et al, 1993;Roelink et al, 1994), induces floor plate in explants of neural tissue (Marti et al, 1995a;Roelink et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The notochord is a midline mesodermal embryonic structure common to all members of the phylum chordata, which has essential functions in patterning the paraxial mesoderm (Herrmann et al, 1990;Dietrich et al, 1993;Pourquie et al, 1993), the neuroectoderm (van Straaten et al, 1988;Bovolenta and Dodd, 1991;Yamada et al, 1993;Placzek et al, 1993), and other tissues (Wiertz-Hoessels et al, 1987;Stern et al, 1991;Danos and Yost, 1995), through notochord-derived signals. In the zebrafish (Danio rerio), systematic mutational analysis of early development has identified several notochord-expressed genes, such as no tail (ntl) and floating head (flh) (Halpern et al, 1993;SchulteMerker et al, 1994;Talbot et al, 1995;Odenthal et al, 1996;Stemple et al, 1996;Currie and Ingham, 1996;Fouquet et al, 1997;Blagden et al, 1997;Amacher and Kimmel, 1998), in which loss-of-function mutations cause defects in the formation and/or maintenance of the notochord and within other tissues.…”
Section: Introductionmentioning
confidence: 99%